PENERAPAN SLOW DEEP BREATHING TERHADAP PENURUNAN KELELAHAN PADA PASIEN GAGAL GINJAL KRONIK DI RUANG RENGAS DENGKLOK RSUD KARAWANG - Serly, Serly; Yumi, Yumi; Deudeu Durrotunafisah (Journal of Innovation Research and Knowledge, 2024)
Patients with chronic kidney disease (CKD) often experience fatigue due to decreased kidney function, which leads to toxin accumulation, anemia, electrolyte disturbances, and sleep disturbances. Excessive fatigue can reduce quality of life and hinder patients' daily activities. One non-pharmacological therapy that can be used to reduce fatigue is Slow Deep Breathing (SDB) exercises, a slow and deep breathing technique that helps increase tissue oxygenation, reduce muscle tension, and stabilize the autonomic nervous system. This study aims to determine the effect of Slow Deep Breathing on reducing fatigue in patients with chronic kidney disease in the Rengasdengklok Ward of Karawang Regional Hospital. This study used a pre-experimental design with a One Group Pretest-Posttest Design approach. The sample consisted of 16 patients with chronic kidney disease undergoing hemodialysis, selected using a purposive sampling technique. The Slow Deep Breathing intervention was carried out for 10–15 minutes per session, twice daily for three consecutive days. Fatigue levels were measured using the Piper Fatigue Scale (PFS) questionnaire before and after the intervention. Data analysis used the Wilcoxon Signed Rank Test with a significance level of 0.05. The average fatigue score before Slow Deep Breathing was 7.25 (severe), and after the intervention, it decreased to 4.18 (moderate). The Wilcoxon test showed a p-value of 0.001 (p < 0.05), indicating a significant effect of Slow Deep Breathing on reducing fatigue in patients with chronic kidney disease. Slow Deep Breathing therapy was effective in reducing fatigue levels in patients with chronic kidney disease in the Rengasdengklok Ward, Karawang Regional Hospital. This exercise can be used as a simple, safe, and beneficial independent nursing intervention to improve patient comfort and quality of life.